Dysregulation of the dopaminergic system secondary to traumatic brain injury: implications for mood and anxiety disorders - Mata-Bermudez, Alfonso; Trejo-Chávez, Ricardo; Martínez-Vargas, Marina; Pérez-Arredondo, Adán; Martínez-Cardenas, Maria de Los Ángeles; Diaz-Ruiz, Araceli; Rios, Camilo; Navarro, Luz (Frontiers in Neuroscience, 2024)
Traumatic brain injury (TBI) represents a public health issue with a high mortality rate and severe neurological and psychiatric consequences. Mood and anxiety disorders are some of the most frequently reported. Primary and secondary damage can cause a loss of neurons and glial cells, leading to dysfunction of neuronal circuits, which can induce imbalances in many neurotransmitter systems. Monoaminergic systems, especially the dopaminergic system, are some of the most involved in the pathogenesis of neuropsychiatric and cognitive symptoms after TBI. In this work, we summarize the studies carried out in patients who have suffered TBI and describe alterations in the dopaminergic system, highlighting (1) dysfunction of the dopaminergic neuronal circuits caused by TBI, where modifications are shown in the dopamine transporter (DAT) and alterations in the expression of dopamine receptor 2 (D2R) in brain areas with dopaminergic innervation, thus establishing a hypodopaminergic state and (2) variations in the concentration of dopamine and its metabolites in biological fluids of post-TBI patients, such as elevated dopamine (DA) and alterations in homovanillic acid (HVA). On the other hand, we show a large number of reports of alterations in the dopaminergic system after a TBI in animal models, in which modifications in the levels of DA, DAT, and HVA have been reported, as well as alterations in the expression of tyrosine hydroxylase (TH). We also describe the biological pathways, neuronal circuits, and molecular mechanisms potentially involved in mood and anxiety disorders that occur after TBI and are associated with alterations of the dopaminergic system in clinical studies and animal models. We describe the changes that occur in the clinical picture of post-TBI patients, such as alterations in mood and anxiety associated with DAT activity in the striatum, the relationship between post-TBI major depressive disorders (MDD) with lower availability of the DA receptors D2R and D3R in the caudate and thalamus, as well as a decrease in the volume of the substantia nigra (SN) associated with anxiety symptoms. With these findings, we discuss the possible relationship between the disorders caused by alterations in the dopaminergic system in patients with TBI.